Change the paths of the Interim Financial Reporting - Taneerananon, Kongrit; Vilalai, Premarat; Thaneerananon, Arisara (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
The Thai interim financial reporting standard has been developed since the introduction of the interim financial statements for the year 1999. Update 2007 Update 2009 Update 2012 Update 2014 Update 2015 Updated 2016 until now, it is an interim financial report. The revised version of the year 2017 has changed in five major areas. 1. The cause of changes caused by international accounting standards that have changed over the years. 2. Name of financial statements used in accounting standard. 3. Presentation of interim financial reporting. 4. Presentation of condensed interim financial reporting. 5. Disclosure of Notes to the financial statements. When users of the financial statements understand the feasibility of interim financial reporting or interim financial statements, they will have an impact on the financial statements of the users. Because of timely information. The results of the quarterly and quarterly financial statements of the Company and its subsidiaries are as follows. Article history : Accepted 14 November 2017 SIMILARITY INDEX = 0.00